Musings about Metaphors and Models: the Need to Put Psychology Together Again - Chaudhary, Nandita (Integr Psychol Behav Sci, 2020)
Zagaria, Andò & Zennaro (2020) raise several issues for the study of the human condition, highlighting the precarious status of psychology on account of a core weakness: The absence of consensus about fundamental concepts. Using the metaphor of a giant, albeit one with feet of clay, the authors develop an argument about how evolutionary psychology is the best possible candidate to advance a unified paradigm on account of theoretical consistency. In this commentary we examine the metaphors and models invoked in the article and suggest alternative perspectives on the grounds that a grand singular solution and consistency in definitions are not urgent requirements for understanding the complexity, diversity, and nuances of the human condition. We argue that plurality and low consensus can be taken as productive and functional; precisely because psychological and cultural phenomena are always characterized by uncertainty in irreversible time. Cultural psychology is a valuable paradigm, inclusive of universal and individual processes in ways that provide more appropriate resolution for cultural pluralism. Every definition of psychological phenomena, however obscure and contested, has arisen from theoretical speculation arising from a specific perspective.